Quality-of-service em arquiteturas eletrônicas veiculares baseadas em rede ethernet automotiva: um mapeamento sistemático - Marques, Wellington Kenidy (2021)
In-vehicle networking are constantly evolving. New types of networks and also new versions of existing networks are embedded, as well as new distributions of electronic units are proposed in vehicular electronic architectures with the development of new electronic systems and innovative demands for embedded applications in vehicles. Currently, the automotive network that enables a large number of applications is the só-called Automotive Ethernet. In order to guarantee the quality of service required by vehicular applications with Ethernet network, Quality-of-Service standards and methodologies are developed. This work presents the implementation of a systematic mapping in order to find updated information on new demands and needs required in vehicular networks as well as the approach or methodology applied to ensure the quality of services. The research method adopted was systematic mapping where 251 research papers were found through a defined search protocol. All works found were classified according to inclusion and exclusion criteria, then filtered by qualification criteria in the field of Computer Science and also filtered by false positives, which means, only articles with state-of-the-art in automotive applications were approved. The six articles resulting from the mapping were analyzed and discussed where it was possible to identify that a large part of the research is related to validation of middlewares and network traffic modeling mechanisms.